STUDY THE FACTORS RELATED TO THE PLACE DELIVERY I.E. PUBLIC HEALTH FACILITY, PRIVATE HEALTH FACILITY AND HOME IN URBAN SLUMS - Sunita Parshuram Pawar; Omprasad B. Damkondwar; Priyanka Sahu (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Background: Childbirth is essentially a healthy and welcome process but is also a moment of great risks.  Objectives: To study the factors related to the place delivery i.e. public health facility, private health facility and home in urban slums.Method: The present community based cross sectional descriptive study was carried among women who had delivered in the period from January 2008 - December 2009. The present study was conducted in the urban slums of a city.  Results: There was no significant difference between proportions of institutional and home deliveries with respect to respondent’s age, their occupational status, religion, family type, caste.Conclusion: The risk factors identified for home deliveries are low educational status of respondents and their husbands and high parity. Respondents with these characteristics should be identified and motivated for institutional delivery.